DETERMINASI KINERJA PEGAWAI PADA PEDIATRIC AND NEURODEVELOPMENTAL TERAPHY CENTER (PNTC) DI SURAKARTA - Suparwi, Suparwi; Darmaesti, Darmaesti (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this study is to determine the influence of competence, work discipline, stress level and work environment on employee performance at the PNTC Special Needs Clinic Surakarta.The research method used in this study is a quantitative method. With a population of all employees of the PNTC Surakarta Special Needs Children's Clinic which totals 30 people. The sampling technique uses a census technique which means that all employees totaling 30 people are sampled in this study. The data collection technique uses a questionnaire. The statistical analysis used in this study is classical assumption test, regression analysis, correlation, hypothesis test using t-test and F test, and determination coefficient analysis.Based on the results of the research conducted, it can be seen that partially competence and work discipline have a positive and significant effect on employee performance. Stress levels have a negative and significant effect on employee performance. The work environment does not have a significant effect on employee performance, simultaneously competence, work discipline, stress level and work environment affect employee performance. Keywords: Competence, Work Discipline, Stress Level, Work Environment, Employee Performance